2014
DOI: 10.1002/jsfa.6581
|View full text |Cite
|
Sign up to set email alerts
|

Determination of volatile compounds in turbot (Psetta maxima) during refrigerated storage by headspace solid‐phase microextraction and gas chromatography–mass spectrometry

Abstract: SPME-GC-MS combined with PCA may be a useful method for monitoring the volatile profile characteristics of turbot during storage, which could be potentially used for freshness evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…Although the possibility for H 2 S production was found, this VOC was not found in the headspace analysis. In contrast, trimethylamine (TMA), which is often considered as an odour marker for the evaluation of seafood freshness (Xu et al ., ), was found in the headspace during storage, although its presence could not be correlated with microbial growth in this study. This is in accordance with results from the biochemical characterization, as all B. thermosphacta and V. salmoninarum isolates were negative for the formation of TMA.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Although the possibility for H 2 S production was found, this VOC was not found in the headspace analysis. In contrast, trimethylamine (TMA), which is often considered as an odour marker for the evaluation of seafood freshness (Xu et al ., ), was found in the headspace during storage, although its presence could not be correlated with microbial growth in this study. This is in accordance with results from the biochemical characterization, as all B. thermosphacta and V. salmoninarum isolates were negative for the formation of TMA.…”
Section: Discussioncontrasting
confidence: 77%
“…All three are methylketones that can be generated from amino acid degradation, Maillard reaction or microbial oxidation. They are known to contribute to floral and sweet flavours (Fratini et al ., ) and have been found as volatiles in headspace of stored seafood such as turbot, precooked prawn, and barnacles (Soncin et al ., ; Fratini et al ., ; Xu et al ., ). 2‐heptanone is formed by Carnobacterium species in cooked and peeled Pandalus borealis shrimp when stored under MAP conditions (Laursen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Six alkanes including decane, undecane, dodecane, tridecane, tetradecane and pentadecane were detected in all samples (Table ). It has been reported that C8‐C19 alkanes did not have important effect on flavour because of their high odour threshold values (Xu et al ., ). One alkene, limonene, generally derived from spices, was also found in samples.…”
Section: Resultsmentioning
confidence: 97%
“…Gas chromatography-mass spectrometry (GC-MS) is a highly effective analytical instrument that is widely used to separate, identify and quantify volatile and semi-volatile compounds in fish products (Sandra, Tienpont, & David, 2003;Wang, Lee, Lewis, Kamath, & Archer, 1999;Xu et al, 2014). In the GC-MS system, analytes are separated due to their different strengths of interaction with the stationary phase, and then the "fingerprint" information of molecules is sensitively identified by the mass spectrometer (Abraham, Poole, & Poole, 1999;Sneddon, Masuram, & Richert, 2007).…”
Section: Introductionmentioning
confidence: 99%